2021
DOI: 10.3390/ma14010201
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Decoration of Ceramic Supports for Highly Effective Enzyme Immobilization—Material Approach

Abstract: A highly effective method was developed to functionalize ceramic supports (Al2O3 powders and membranes) using newly synthesized spacer molecules. The functionalized materials were subsequently utilized for Candida antarctica lipase B enzyme immobilization. The objective is to systematically evaluate the impact of various spacer molecules grafted onto the alumina materials will affect both the immobilization of the enzymes and specific material surface properties, critical to enzymatic reactors performance. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…After that, the grafted Al 2 O 3 was centrifuged and washed with dichloromethane, aqueous HCl (pH 2-3), a solution of NaHCO 3 , and distilled water (five times in portions of 10 mL). The grafted powder of Al 2 O 3 was dried over 24 h at 52 • C [40].…”
Section: Procedures For Grafting Of Aluminum Oxidementioning
confidence: 99%
“…After that, the grafted Al 2 O 3 was centrifuged and washed with dichloromethane, aqueous HCl (pH 2-3), a solution of NaHCO 3 , and distilled water (five times in portions of 10 mL). The grafted powder of Al 2 O 3 was dried over 24 h at 52 • C [40].…”
Section: Procedures For Grafting Of Aluminum Oxidementioning
confidence: 99%
“…2021 yılında işlevselleştirilmiş alümina malzemesi Candida antarctica lipaz B enzimi immobilizasyonu için kullanıldı. Alümina malzemesi üzerine adsorbsiyon yöntemiyle immobilize edilen lipaz B'nin, spesifik enzim aktivitesi >%97 olarak verilmiştir (28).…”
Section: Aktivite Ve Protein Değerleriunclassified
“…The obtained results indicated that the specific enzyme activity was much higher for those samples which were functionalized with longer modifiers. The enzyme loading efficiency was found to depend on different factors, such as type of spacer molecules, their chemical composition and the length of the chains, along with enzyme interactions with the surfaces of the carriers [128]. However, these approaches are usually more expensive and complicated when compared with the physical techniques [117].…”
Section: Heterogeneous Enzymatic Reactions For the Remediation Of Phenolic Wastewatersmentioning
confidence: 99%